2022
DOI: 10.1080/21655979.2022.2062106
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CC chemokine ligand (CCL) 20 by miR-143-5p alleviate lead poisoning-induced renal fibrosis by regulating interstitial fibroblasts excessive proliferation and dysfunction

Abstract: Environmental lead contamination can cause chronic renal disease with a common clinical manifestation of renal fibrosis and constitutes a major global public health threat. Aberrant proliferation and extracellular matrix (ECM) accumulation in renal interstitial fibroblasts are key pathological causes of renal fibrosis. However, the mechanism underlying lead-induced kidney fibrosis remains unclear. The present study analyzed gene expression prolifes in lead acetate-treated primary mice renal interstitial fibrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…CCL20 is a chemokine that regulates inflammation, 32 and miR-143-5p can bind with CCL20 to affect the development of renal fibrosis. 28 In this study, the miRanda algorithm predicted the binding site of homo sapiens (hsa)- miR-143-5p and CCL20, as shown in Figure 5A. The dual luciferase reporter gene system was used to verify the targeting relationship between miR-143-5p and CCL20, and the results showed that miR-143-5p significantly inhibited the luciferase activity of wild-type CCL20, but had no effect on the luciferase activity of mutant CCL20 (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…CCL20 is a chemokine that regulates inflammation, 32 and miR-143-5p can bind with CCL20 to affect the development of renal fibrosis. 28 In this study, the miRanda algorithm predicted the binding site of homo sapiens (hsa)- miR-143-5p and CCL20, as shown in Figure 5A. The dual luciferase reporter gene system was used to verify the targeting relationship between miR-143-5p and CCL20, and the results showed that miR-143-5p significantly inhibited the luciferase activity of wild-type CCL20, but had no effect on the luciferase activity of mutant CCL20 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…27 MiR-143-5p can affect renal fibrosis by targeting CCL20. 28 However, whether targeted regulation of CCL20 by miR-143-5p is involved in the process of AAA remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Marisa et al found that CXCL2 was downregulated in diabetic rats under hypoxic conditions [ 48 ]. In addition, targeting CCL20 could alleviate renal fibrosis through regulating fibroblast proliferation and suppressing collagen I expression [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines stimulate the migration of immune cells and increase the production and activity of adhesion molecules that contribute to fibrosis and kidney damage [ 36 , 57 ]. In humans, increased expression of the IL-8 , CCL4 , and CCL20 genes are involved in the pathogenesis of renal diseases [ 58 60 ]. Our data showing high levels of pro-inflammatory cytokine and chemokine gene expression in heat-stressed hens indicates that the release of these cytokines contributes to the progression of renal fibrosis and failure.…”
Section: Discussionmentioning
confidence: 99%